2020
DOI: 10.1038/s41421-020-00211-8
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA lncLy6C induced by microbiota metabolite butyrate promotes differentiation of Ly6Chigh to Ly6Cint/neg macrophages through lncLy6C/C/EBPβ/Nr4A1 axis

Abstract: Macrophages are mainly divided into two populations, which play a different role in physiological and pathological conditions. The differentiation of these cells may be regulated by transcription factors. However, it is unclear how to modulate these transcription factors to affect differentiation of these cells. Here, we found that lncLy6C, a novel ultraconserved lncRNA, promotes differentiation of Ly6Chigh inflammatory monocytes into Ly6Clow/neg resident macrophages. We demonstrate that gut microbiota metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…The ability of signaling molecules released by the microbiota to enter the circulation also allows resident bacteria in the gut to already modulate the immune system during immune cell development during hematopoiesis and, in that way, influence the response to infection [ 1 , 47 ]. Indeed, the SCFA butyrate was shown to promote the differentiation of bone marrow monocytes from an inflammatory phenotype to a more tolerogenic phenotype [ 48 ]. Bone marrow cells also express a variety of PRRs and are susceptible to circulating MAMPs with differential effects dictated by PRR expression and MAMP availability [ 49 ].…”
Section: Protection From Infections: the Effect Of The Gut Microbimentioning
confidence: 99%
“…The ability of signaling molecules released by the microbiota to enter the circulation also allows resident bacteria in the gut to already modulate the immune system during immune cell development during hematopoiesis and, in that way, influence the response to infection [ 1 , 47 ]. Indeed, the SCFA butyrate was shown to promote the differentiation of bone marrow monocytes from an inflammatory phenotype to a more tolerogenic phenotype [ 48 ]. Bone marrow cells also express a variety of PRRs and are susceptible to circulating MAMPs with differential effects dictated by PRR expression and MAMP availability [ 49 ].…”
Section: Protection From Infections: the Effect Of The Gut Microbimentioning
confidence: 99%
“…The underlying processes by which the gut microbiome contributes to CRC have been the subject of various research, which have shown that numerous pathogenic bacteria and metabolites of the gut microbiome can affect the progression of CRC by controlling the expression of lncRNAs [ 17 , 36 , 37 ]. By upregulating LINC00152, a gene associated with intestinal inflammation, cancer cell migration, and invasion, Wang et al discovered that Salmonella typhimurium infection affected the lncRNAs expression in intestinal epithelial cells [ 36 ].…”
Section: The Development Of Crc Promoted By the Disturbance Of The Gu...mentioning
confidence: 99%
“…According to Chen et al, Fusobacterium nucleatum infection upregulates the lncRNAs Keratin7-antisense (KRT7-AS) and Keratin7 (KRT7) by triggering the NF-κB pathway to promote CRC metastasis [ 17 ]. Conversely, the gut microbiome metabolite butyrate-induced lncRNA LncLy6C suppressed intestinal inflammation, thus lowering the risk of CRC, according to the research by Gao et al [ 37 ]. Therefore, it is reasonable to assume that gut microbiome disorders can influence CRC development via mediating lncRNAs.…”
Section: The Development Of Crc Promoted By the Disturbance Of The Gu...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of microbes to release signaling molecules into the bloodstream can modulate the host's response to infections via the regulation of immune cell development (21). For instance, butyrate secreted by bacteria promotes the differentiation of monocytes in the bone marrow to a tolerogenic phenotype (22). Moreover, it was recently showed that some bacterial species could decrease the level of corticosterone in the blood which could improve the function of the immune system during the infection (23).…”
Section: Gut Microbiota and Immune System In Health And Disease Specifically Infectionsmentioning
confidence: 99%